2015
DOI: 10.1016/j.mspro.2015.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on Structural and Optical Properties of Dip and Spin coated ZnO Thin Films

Abstract: This paper reports the influence of annealing temperature on crystalline size, film roughness, surface morphology and photoluminescence properties of ZnO thin films prepared by dip and spin coating techniques. Thin films were annealed at 400 C and 500 C for one hour each and their structural properties were studied using XRD, AFM and SEM. The coatings were characterized for photoluminescence using UV-visible Spectrometer. The films produced by both the methods conformed to hexagonal wurtzite structure. The gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
(14 reference statements)
3
14
0
1
Order By: Relevance
“…5. The crystallinity (determined from the soware provided by the manufacturer, known as Diffrac Suite Version 4 (Diffrac.eva)) increase as the temperature increases consistent with previous reports by other workers 39,40 and is dependent on whether the lms were annealed in vacuum or air. Air annealed samples have higher crystallinity as shown in the Table 2.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…5. The crystallinity (determined from the soware provided by the manufacturer, known as Diffrac Suite Version 4 (Diffrac.eva)) increase as the temperature increases consistent with previous reports by other workers 39,40 and is dependent on whether the lms were annealed in vacuum or air. Air annealed samples have higher crystallinity as shown in the Table 2.…”
Section: X-ray Diffractionsupporting
confidence: 87%
“…There are various methods that can be used in order to synthesize thin films such as sol-gel method, sputtering, spray pyrolysis [4] and laser deposition. Sol-gel method is widely used because of advantages like it is economical, ease of deposition, ease of controlling the composition of the films and controlling doping percentage [5][6][7]. Yogesh et al [8] studied the properties of self aligned CZO films and found out that resistance decreased with doping of Copper in ZnO films.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that the existence of aluminum did not change the electronic structure or optical characteristics. G. P. Daniel [20] et al deposited ZnO on corning glass by radio frequency (RF) magnetron sputtering. J. Bhattacharya [21] et al fabricated polymer solar cells based on AZO thin film as a counter electrode which could enhance the current density.…”
Section: Introductionmentioning
confidence: 99%